2021
DOI: 10.1088/1755-1315/850/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

CFD analysis on the influence of angle of attack on vertical axis wind turbine aerodynamics

Abstract: The Angle of Attack (AOA) in a Vertical Axis Wind Turbine (VAWT) plays an important role in determining the forces and the power generated by the wind turbine. It is difficult to find the suitable AOA due to the complex and constantly changing wind flow patterns. In this paper, we have performed CFD simulations using Ansys Fluent software, based on the constantly changing AOA. The CFD simulations were conducted by selecting a suitable range of AOA and the velocity of the wind. The selected range of AOA varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The idea of a transportation system using evacuated tubes has several benefits, including low energy consumption, increased speed, lower noise pollution, lower aerodynamic resistance, etc. [8][9][10]. Zhang et al, [11] outlined a few important problems with evacuated tube transportation systems that need to be taken into account during the design phase.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The idea of a transportation system using evacuated tubes has several benefits, including low energy consumption, increased speed, lower noise pollution, lower aerodynamic resistance, etc. [8][9][10]. Zhang et al, [11] outlined a few important problems with evacuated tube transportation systems that need to be taken into account during the design phase.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kamath et al, [5] studied the effect of radiator angle and radiator seal using CFD and concluded that an angled radiator without a seal yields higher mass flow rate of air through the radiator. Srivastava et al, [6] optimized a diverging-converging type sidepod using internal CFD simulations and concluded that a small inlet area results in increased mass flow rate of air through the radiator. Harish and Venkatasubbaiah [7] and Waman and Harish [8] worked on developing a complete aerodynamic package for an FSAE car and had also validated their results with experimental setups.…”
Section: Introductionmentioning
confidence: 99%